1998
DOI: 10.1007/s005340050068
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgical treatments and prognostic factors for hepatic hilar bile duct cancer

Abstract: Results of surgical treatments for 57 patients who underwent resection for hepatic hilar bile duct cancer between 1984 and 1997 were studied. Bile duct resection was performed in eight patients, and combined resection of bile duct and liver was performed in 49 patients, of whom vascular reconstruction was added in 15 patients and pancreatoduodenectomy (PD) in six patients. All the operations of bile duct resection that were not combined with hepatectomy were non-curative. In the patients who underwent combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recent evidence suggests that extended lymphadenectomy may prolong survival in selected patients with gallbladder cancer 36,37 or hilar cholangiocarcinoma. [5][6][7][8]14 Boniest et al 38 reported that regional lymphadenectomy in the hepatoduodenal ligament was effective for improving outcome in gallbladder cancer patients without overt nodal metastasis. In the present study, nodal micrometastasis occurred in about one fourth of patients with histologically node-negative hilar cholangiocarcinoma, while most micrometastases were found in N2 rather than N1 regional lymph node groups.…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence suggests that extended lymphadenectomy may prolong survival in selected patients with gallbladder cancer 36,37 or hilar cholangiocarcinoma. [5][6][7][8]14 Boniest et al 38 reported that regional lymphadenectomy in the hepatoduodenal ligament was effective for improving outcome in gallbladder cancer patients without overt nodal metastasis. In the present study, nodal micrometastasis occurred in about one fourth of patients with histologically node-negative hilar cholangiocarcinoma, while most micrometastases were found in N2 rather than N1 regional lymph node groups.…”
Section: Discussionmentioning
confidence: 98%
“…With the recent advances in the anatomic knowledge of the liver and hepatic hilus, improved diagnostic and surgical techniques, and refinements in pre-and postoperative management, aggressive liver and bile duct resection has frequently been performed for hilar cholangiocarcinoma with varying degrees of success [1][2][3][4][5][6][7][8][9][10]. Several surgeons have reported that hepatectomy with en bloc resection of the caudate lobe and the extrahepatic bile duct offers a better chance of long-term survival by producing tumorfree margins in the intrahepatic bile ducts [1,3,4,7,9,10]. Postoperative morbidity and mortality rates after hepatectomy, however, remain high [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Bile duct cancers are generally associated with an unfavorable prognosis,7,8 and several prognostic factors have been reported. Papillary lesions, which are uncommon, have a better prognosis than other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Inadvertent division of the subvesical duct during cholecystectomy may cause postoperative leakage of bile. 6 Bile duct cancers are generally associated with an unfavorable prognosis, 7,8 and several prognostic factors have been reported. Papillary lesions, which are uncommon, have a better prognosis than other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%